Antibiotic prescribing in primary care: first choice and restrictive prescribing are two different traits. Issue 2 (2nd April 2007) - van Roosmalen, M S; Braspenning, J C C; De Smet, P A G M; Grol, R P T M
Abstract : Objective: To investigate the quality of antibiotic prescribing in primary care using quality indicators and the relatedness of these indicators. To determine the influence of general practice and practice population characteristics on the indicator scores. Methods: Data on performance were collected during the Second National Survey of General Practice over 1 year between May 2000 and April 2002 in The Netherlands. The study was carried out in 104 computerised general practices, comprising 195 general practitioners and about 400 000 patients. From a preliminary set of quality indicators on antibiotic prescribing (n = 15), eight were selected covering various medical conditions. Indicator scores were derived. A factor analysis was performed to examine the relatedness of these indicators. Composite scores were calculated for the indicators loading on the same factor. The influence of general practice and practice population characteristics on the quality of antibiotic prescribing was investigated. Results: Considerable variation was found between indicator scores (32.8–94.2%) and between practices. The factor analysis discovered two interpretable factors—namely, "first choice prescribing" and "restrictive prescribing". The composite scores were 64% and 68%, respectively. No significant correlation was found between the two composite scores. Practice and population characteristics explained only a small proportion of the variance between practices. Conclusions: Although different quality indicators on antibiotic prescribing are grouped together over several medical conditions, there is large variation between those indicators. General practices performing well on first choice prescribing do not automatically perform well on restrictive prescribing. There is room for improvement on both aspects of prescribing. The variation between practices is clearly present and should be further investigated.